2017
DOI: 10.1159/000456066
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Multidrug Resistance via Enhancement of Epidermal Growth Factor-Like Domain 7 Expression in Non-Small Lung Cancer Cells

Abstract: Chemotherapy is widely used in non-small cell lung cancer (NSCLC) treatment, yet multidrug resistance (MDR) is a major chemotherapeutic obstacle in both resectable and advanced NSCLC. Epidermal growth factor-like domain 7 (EGFL7), also known as vascular endothelial stain, is an endothelial cell-derived secreted factor that regulates vascular tube formulation. The aim of this study was to investigate the potential relationships between EGFL7 and MDR in NSCLC cells. We first obtained the CDDP-based MDR phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…It is well known that hypoxia induces resistance among various tumors. Previous reports showed that hypoxia can enhance drug resistance in non-small lung cancer cells [4]. Hypoxia-inducible factors are involved in chemotherapy resistance of breast cancer stem cells [5].…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that hypoxia induces resistance among various tumors. Previous reports showed that hypoxia can enhance drug resistance in non-small lung cancer cells [4]. Hypoxia-inducible factors are involved in chemotherapy resistance of breast cancer stem cells [5].…”
Section: Introductionmentioning
confidence: 98%
“…Lung cancer, one of the most common cancer types in women and men, is currently the predominant cause of cancer-related deaths worldwide, resulting in more than one million deaths worldwide annually [ 1 ]. Non-small cell lung cancer (NSCLC) comprises almost 85% of all lung cancer cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…contributing to radio-or chemotherapeutic resistance (Klein et al, 2017;Shen et al, 2017). It thus serves as a prognostic marker of poor clinical outcome and the hypoxic microenvironment has become a focal area of cancer research and treatment.…”
mentioning
confidence: 99%